Adapting automated treatment planning configurations across international centres for prostate radiotherapy. (April 2019) - Roach, Dale; Wortel, Geert; Ochoa, Cesar; Jensen, Henrik R.; Damen, Eugene; Vial, Philip; Janssen, Tomas; Hansen, Christian Rønn
Abstract: Background and purpose: Automated configurations are increasingly utilised for radiotherapy treatment planning. This study investigates whether automated treatment planning configurations are adaptable across clinics with different treatment planning protocols for prostate radiotherapy. Material and methods: The study comprised three participating centres, each with pre-existing locally developed prostate AutoPlanning configurations using the Pinnacle 3 ® treatment planning system. Using a three-patient training dataset circulated from each centre, centres modified local prostate configurations to generate protocol compliant treatment plans for the other two centres. Each centre applied modified configurations on validation datasets distributed from each centre (10 patients from 3 centres). Plan quality was assessed through DVH analysis and protocol compliance. Results: All treatment plans were clinically acceptable, based off relevant treatment protocol. Automated planning configurations from Centre's A and B recorded 2 and 18 constraint and high priority deviations respectively. Centre C configurations recorded no high priority deviations. Centre A configurations produced treatment plans with superior dose conformity across all patient PTVs (mean = 1.14) compared with Centre's B and C (mean = 1.24 and 1.22). Dose homogeneity was consistent between all centre's configurations (mean = 0.083, 0.077, and 0.083 respectively). Conclusions: This study demonstrates that automated treatment planning configurations can be shared and implemented across multiple centres with simple adaptations to local protocols.